THE RELATIONSHIP OF PARENTS' PARENTING PATTERNS WITH BULLYING BEHAVIOR IN ADOLESCENT AGES 13-18 YEARS OLD IN KP. JEGANG RW 001 BOJONGMANGU - Siti Aminah; Dinda Nur F. H. B.; Ani Anggraini S. (Rena Cipta Mandiri, 2023)
Abstract: Cases of bullying in Indonesia ranks first, namely as much as 34%. The existence of bullying seems to be underestimated, so maybe only a few are aware of the dangers of the existence of bullying. The danger of bullying can result in a lack of confidence or even loss of life. One of the factors that cause bullying behavior is parenting factors. Research Objectives: This study aims to determine the relationship between parenting and bullying behavior in adolescents aged 13-18 years in Kp.Jegang RW 001 Bojongmangu Village. Research Methods: The method used in this research is quantitative research, which is analytic with a cross-sectional design. The sampling technique in this study is total sampling with a total of 94 teenagers in 2022. Research Results: The results of the bivariate analysis show that there is a relationship between parenting patterns and bullying behavior in adolescents aged 13-18 years in Kp.Jegang RW 001 Bojongmangu Village with the results chi-square P-Value (0.00) < a (0.05). The majority of poor parenting has as many as 52 respondents (55.3%) and no bullying behavior as many as 52 respondents (55.3%). Conclusion: The results of research analysts that there is a relationship between parenting patterns and bullying behavior in adolescents aged 13-18 years in Kp.Jegang RW 001 Bojongmangu Village.